2016
DOI: 10.1002/cncr.30081
|View full text |Cite
|
Sign up to set email alerts
|

Patient experience and quality of urologic cancer surgery in US hospitals

Abstract: Using Nationwide Inpatient Sample and HCAHPS data, the authors found a limited association between patient experience and surgical outcomes. For urologic cancer surgery, patient experience may be optimally viewed as an independent quality domain rather than a mechanism with which to improve surgical outcomes. Cancer 2016;122:2571-8. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 28 publications
(45 reference statements)
1
31
0
Order By: Relevance
“…These patient satisfaction data have been previously used as a tool to evaluate associations between outcomes in surgery. 23 …”
Section: Institutional Variablesmentioning
confidence: 97%
“…These patient satisfaction data have been previously used as a tool to evaluate associations between outcomes in surgery. 23 …”
Section: Institutional Variablesmentioning
confidence: 97%
“…Participants rate the frequency of experiencing each of the following: difficulty understanding the doctor because of an accent or way English was spoken; not understanding medical words; doctor speaking too fast; doctor using different aids when explaining things; doctor ignoring information provided; being interrupted by the doctor when talking; doctor showing interest in questions and concerns; satisfaction with answers provided to questions; and being encouraged to ask questions or discuss concerns. The CAHPS health literacy questions are a validated measure for consumers to provide feedback on their experiences of communication with providers (Lake et al 2005;Horowitz et al 2012;Agency for Healthcare Research and Quality 2016;Shirk et al 2016;Thiels et al 2016). The BHLS questions and the CAHPS questions have not been validated for their use with Aboriginal and Torres Strait Islander people.…”
Section: Data Collection and Recruitmentmentioning
confidence: 99%
“…3 The findings of their study indicate that some of the HCAHPS measures for patient satisfaction are modestly associated with a prolonged length of stay and nursingsensitive complications at high-performing hospitals compared with low-performing hospitals. For example, patient communication with nurses and physicians, discharge information, and explanation of medications were found to be associated with a lower risk of prolonged hospitalization.…”
mentioning
confidence: 96%
“…1 Second, several studies have consistently shown that larger hospitals have higher HCAHPS scores across different surgical procedures, which is likely attributable to the availability of a greater number of providers, nurses, and resources. 2,3,5 Conversely, the use of such patientreported outcome measures and linking them to financial incentives and penalties may expose hospitals with limited resources to greater financial risk. In particular, safety-net hospitals, which provide a greater percentage of medical care to vulnerable patient populations, have been shown to have lower HCAHPS scores.…”
mentioning
confidence: 99%